Unrecognised coeliac disease among men and women undergoing fertility treatment: A screening study. Issue 10 (December 2018) - Grode, Louise B; Agerholm, Inge E; Humaidan, Peter; Parkner, Tina; Bech, Bodil H; Ramlau-Hansen, Cecilia H; Jensen, Thomas M
Background: Coeliac disease is an autoimmune disease triggered by dietary gluten and has been associated with several conditions influencing female and male reproduction. Due to unspecific symptoms, coeliac disease can be unrecognised for years. Objective: To estimate the prevalence of unrecognised coeliac disease among couples referred to fertility treatment. Methods: Cross-sectional screening for coeliac disease in men and women referred to fertility treatment using IgA tissue transglutaminase antibodies as a marker of coeliac disease and small-bowel biopsies to confirm the diagnosis. Participants answered a questionnaire on gluten intake, gastrointestinal symptoms and reproductive history. Results: A total of 893 participants (51% women) were screened and eight were coeliac disease antibody positive. Small-bowel biopsies were obtained from seven antibody positive participants and unrecognised coeliac disease was confirmed in one woman and three men, corresponding to a prevalence of 0.45% (95% confidence interval 0.12–1.14). The total prevalence, combining already diagnosed and unrecognised CD cases, was 0.63% (95% confidence interval 0.29–1.12). Conclusion: The prevalence of unrecognised coeliac disease in a group of infertile patients was equivalent to that of the Danish general population and low compared with that observed in the majority of other screening studies of infertile patients. Surprisingly, it should be noted that more men than women had coeliac disease. This result does not support a need for routine screening among infertile patients.